Sjogren’s syndrome related autoimmune encephalopathy presenting as depression and involuntary agitation in a 15-year-old girl: a case report - Lee, Yu-Tung; Wu, Chao-Yi; Chou, I-Jun; Liu, Chun-Hao (Frontiers in Immunology, 2023)
Introduction: Sjogren’s syndrome is an autoimmune disease that commonly involves exocrinopathy. Although studies have reported psychiatric manifestations resulting from Sjogren’s syndrome, few studies have focused on such manifestations in pediatric patients. Herein, we present a case of an adolescent girl with depression and involuntary self-harm behaviors related to Sjogren’s syndrome with central nervous system involvement. Case presentation: A 15-year-old girl, with an underlying history of epilepsy, developed depressive symptoms of a year’s duration, accompanied by three seizure episodes and involuntary self-harm behaviors. The self-harm behaviors, which included head banging and arm scratching, were sudden onset, involuntary, and unable to be recalled afterwards. After admission to our ward, the patient was positive for serum antinuclear antibodies and Schirmer’s test. Moreover, 24-hour electroencephalography revealed epileptiform discharges during the mood swing episodes. Positive findings for antinuclear antibodies and anti-SSA antibodies in both serum and cerebrospinal fluid, suggested central nervous system involvement in Sjogren’s syndrome. After rituximab treatment, her mood became euthymic, and her involuntary self-harm behaviors ceased. Conclusion: Central nervous system involvement leading to psychiatric presentations has rarely been reported in adolescents with Sjogren’s syndrome. When treating adolescent patients with involuntary self-harm behaviors and neurological symptoms, it is crucial to consider autoimmune encephalitis related to Sjogren’s syndrome in the differential diagnosis.